Perioperative therapy in renal cancer in the era of immune checkpoint inhibitor therapy. Issue 3 (May 2021) - Kuusk, Teele; Abu-Ghanem, Yasmin; Mumtaz, Faiz; Powles, Thomas; Bex, Axel
Abstract : Purpose of review: Immune checkpoint inhibitor (ICI) combination therapy has revolutionized therapy of metastatic renal cancer. The success of immunotherapy has renewed an interest to study these agents in adjuvant and neoadjuvant settings and prior to cytoreductive nephrectomy. This narrative review will give an overview of ongoing trials and early translational research outcomes. Recent findings: In nonmetastatic renal cell carcinoma (RCC), five phase 3 adjuvant and neoadjuvant trials with ICI monotherapy or combinations are ongoing with atezolizumab (IMmotion 010; NCT03024996), pembrolizumab (KEYNOTE-564; NCT03142334), nivolumab (PROSPER; NCT03055013), nivolumab with or without ipilimumab (CheckMate 914; NCT03138512) and durvalumab with or without tremelimumab (RAMPART; NCT03288532). Phase 1b/2 neoadjuvant trials demonstrate safety, efficacy and dynamic changes of immune infiltrates and provide rationales for neoadjuvant trial concepts as well as prediction of response to therapy. In primary metastatic RCC, two phase 3 trials investigate the role of deferred cytoreductive nephrectomy following pretreatment with ICI combination (NORDICSUN; NCT03977571 and PROBE; NCT04510597). Summary: The outcomes of the major phase 3 trials are awaited as early as 2023. Meanwhile, translational data from phase 1b/2 studies enhance our understanding of the tumour immune microenvironment and its dynamic changes.